Analisis Faktor Penghambat dan Pendukung Pendayagunaan Tanaman Gonda sebagai Produk Wisata Kuliner Khas Desa Bongan - I Gusti Ayu Ari Agustini (Yayasan Literasi Sains Indonesia, 2022)
This study aimed at finding out the supporting and hampering factors in utilizing Gonda plant as the culinary product of Bongan Village. This research was a descriptive qualitative research and using observation, interviews, and literature study to collect the data. It was done in Bongan village. Based on the results of analysis, the supporting factors are Gonda plants are unseasonal plants that can be harvested many times in a year, there is strong determination and commitment, and the support of the Ministry of Tourism and Creative Economy in collaboration with Politeknik Internasional Bali. Meanwhile the hampering factors are the the limited numbers of people utilizing Gonda, the limited ability to see the business opportunities, the lack of ability and willingness, the chips and gonda tea need to be improved, the packaging is still simple, the cleanliness of the production area, and there is no scientific test results of Gonda plants.